The Biology of the Spider Wasp, Pepsis Thisbe (Hymenoptera: Pompilidae) From Trans Pecos, Texas. II. Temporal Patterns of Activity and Hunting Behavior With Special Reference to the Effects of Experience - Fred Punzo (Psyche: A Journal of Entomology)
The temporal pattern of activity and hunting behavior of the spider wasp, Pepsis thisbe, from Trans Pecos, Texas are described. Females exhibited a bimodal pattern with peak periods of hunting activities occurring between 0800–0959 and 1600–1759 hr. The lowest levels of activity (1100–1359 hr) occurred when ambient temperatures exceeded 38℃. Activity declined abruptly after 1800 hr indicating a strong preference for diurnal activity in this species. The behavioral components of the hunting sequence consist of an initial approach and antennation of the host, grooming, antennation and paralyzation followed in some cases by lapping, ovipositiom burial of the host, and closure of the nest. The time required to complete the hunting sequence was recorded for both field and laboratory encounters between a wasp and spider. The amount of time required by a female wasp to complete the initial approach and antennation-paralyzation sequences decreased significantly as a function of increasing encounter experience. The spider is stung most frequently (>80%) through the intersegmental membrane between the sternum and coxa of the first leg. Whether or not a wasp exhibits lapping behavior is determined by the amount of time spent in flight searching for a host burrow.